EFFECT OF PHOTOPERIOD AND GROWTH REGULATORS ON PHYSIOLOGY AND ROOTING OF MICROPROPAGATED EUSTOMA GRANDIFLORUM (RAF.) SHINN - G. C. Popescu; M. Popescu2 (Journal of Animal and Plant Sciences, 2020)
Lisianthus [Eustoma grandiflorum (Raf.) Shinn] is an important ornamental plant with high potential for Romanian cut flower market. The plant material tested and evaluated in this research included three cultivars of Eustoma grandiflorum. The purpose of our study was to evaluate the effect of photoperiod and plant growth regulator concentrations in growing medium on physiology and rooting of micropropagated Lisianthus. The shoot tip explants from Eustoma grandiflorum were cultured on half strength macro and micro salts of Murashige and Skoog basal medium supplemented with different concentrations of indole–3 butyric acid (IBA), indolyl-3-acetic acid (IAA), and naphthalene acetic acid (NAA). The plantlets were treated with four concentrations of each growth regulator in 16-hour and 12-hour photoperiod conditions. The main physiological parameters and characteristics of rooting during in vitro phase were analyzed in order to assess the proper photoperiod and growing media. The experiment was carried out in a randomized complete block design with three replications per treatment. For each treatment we used five vessels. The statistical analysis was performed using the analysis of variance – Duncan test and t-test for independent samples with SPSS 16.0 software. The percentage of shoots in all cultivars that produced roots increased with higher IBA concentrations, ranging from 0.2 mg l-1 to 0.6 mg l-1 for both levels of photoperiod. The longest roots formed on the in vitro plantlets in the rooting phase were recorded on the growing media supplemented with 0.3 mg l-1 NAA. The increase of NAA concentration from 0.1 mg l-1 to 0.3 mg l-1 positively influenced the growth of the roots for all the varieties in both types of photoperiods. Our outcomes emphasized that there were no statistical differences in photosynthetic pigments between the plantlets treated with 12-hour or 16-hour photoperiod (p>0.05). According to these results, the testing of different photoperiods led to the conclusion that the operation of the growth chamber in 12-hour of light had stronger effects in specific conditions, also allowing a 4-hour light energy saving, which reduces energy costs by about 25% in the in vitro rooting phase. The results indicated an optimization of lisianthus in vitro micropropagation and demonstrated the efficiency of 12-hour photoperiod. Therefore, the present study introduces a useful and an effective protocol for in vitro propagation of lisianthus.
Keywords: growing media; growth regulators; in vitro culture; physiology and photoperiod; Lisianthus [Eustoma grandiflorum (Raf.) Shinn]